A mannose-recognizable chemosensor using gold nanoparticles functionalized with pradimicin, a nonpeptidic mannose-binding natural product. Issue 18 (6th May 2015) - Enomoto, Masaru; Igarashi, Yasuhiro; Sasaki, Masahide; Shimizu, Hiroki
Abstract: By making use of the distance-dependent optical properties of gold nanoparticles as well as the mannose (Man)-specific binding ability of pradimicin (PRM), we have successfully developed a Man-recognizable chemosensor. The dissociation constant of the chemosensor for Man was estimated to be approximately 10 μM, which was ten times lower than that of PRM itself. This result may be attributed to a cluster effect. Therefore, the chemosensor was capable of recognizing Man residues that have not yet been identified as the binding sites for PRM. Graphical abstract: